Research Information Systems - Juozapavičius, A. (Nonlinear Analysis: Modelling and Control, 1997)
This survey presents an overview and study of features and capabilities of information systems, which are suitable to support research work in all stages of it: developing of ideas, design, simulation, calculation, searching and exchanging of information, etc. It discusses a wide-spread attempts, purposes (and objectives) to integrate such systems, relying on capabilities of Internet. The role of methods like multimedia, algorithms of spatial data, data compression, telecommunication, in design and developing research information systems, are discussed too. This servey reflects main points in integration of information search and retrieval procedures with other research activities.